Popular vocabulary in Chinese cyberspace / Bok Check Meng - Bok, Check Meng
At the end of 20th century, with the popularity of the Internet, popular vocabulary in Chinese cyberspace has emerged as the times require. It has become the focus of linguists' research. The use of popular cyber vocabulary in modern people's lives is expanding. As a product of language development to a certain stage, popular cyber vocabulary has its own characteristics. This book starts from the characteristics of popular cyber vocabulary and explains its application in modern communication and its difference with modern Chinese. This book combines the current popular cyber vocabulary to illustrate the main forms of popular cyber vocabulary from four language items: phonetics, vocabulary, grammar and semantics. For example, cyber homophonic words are an important part of popular cyber vocabulary. At present, the newly emerging cyber homophones in cyberspace can be divided into four types: alphabetic, Chinese character, numeral and hybrid. The emergence of these vocabularies has a certain impact on people's language expression, language communication and entertainment of online communication, but cyber homophonic words have ambiguity and uncertainty, and need to be further standardised. This paper also expounds the popular cyber symbols, and studies the classification and characteristics of popular cyber symbols. It is found that there are more and more indecent and vulgar popular cyber vocabularies in the cyberspace. Therefore, it is recommended that the decency of this popular cyber vocabulary be especially important.